IMPLEMENTASI MANAJEMEN KURIKULUM MADRASAH MUROTTILIL QUR`AN AL-RIFA`IE 2 MALANG - Akhmad Ulul Albab (STAI Ma'had Aly Al-Hikam Malang, 2019)
This thesis aims to examine the management process applied in the Madrasah Murottilil Qur'an Al-Rifa'ie 2 Malang. Beginning with the curriculum planning process, implementing the curriculum, and how to evaluate the curriculum of the Madrasah Murottilil Qur'an Al-Rifa'ie 2 Malang. This research aims to find out and describe the managerial process of the curriculum, and the inhibiting factors in the implementation of efforts to achieve the vision, mission that has been set.This thesis is a report on the results of field research using a qualitative descriptive method with a case study research approach that takes place at the Al-Rifa'ie 2 Malang Boarding School.Data collection is done by interview, observation, and documentation. Data analysis is done by reducing data, then presenting data, and finally from the compiled data conclusions are drawn. Checking the validity of the data is done with credibility which includes Triangulation, peer checking, extension of observation time, increasing perseverance.The results of the analysis show that the curriculum management implemented by p Madrasah Murottilil Qur'an Al-Rifa'ie 2 At the planning stage, the process carried out was planning the implementation time, the learning program, making the academic calendar, and how the evaluation was held. At the implementation stage, it starts with a new santri test, conducts learning and conducts an ascension test. The evaluation process is carried out at least 2x in one month, and 1 and after one semester.